Slipping through the cracks : intervention strategies for clients with multiple addictions and disorders - Sanders, Mark, 1960- (Deerfield Beach, Fla. : Health Communications, 2011)
"Clients who have multiple addictions and disorders are more difficult to engage and treat than clients with a single disorder. Many of the current systems are ill-equipped to address the myriad challenges of these clients--their relapse and recidivism rates are higher, and many of these clients tend to slip through the cracks, often going back and forth among addictions treatment, psychiatric and medical hospitalizations, and incarceration. Too many difficult-to-reach clients are at risk for relapse because their practitioners lack effective, innovative strategies for this unique client base who remain part of a revolving-door syndrome. Now, Certified Alcohol and Drug Addictions Counselor Mark Sanders, LCSW, offers specific strategies to assist therapists and counselors who work with difficult and at-risk populations..."--Publisher description.
Strategies for engaging resistant clients -- Integrating the addictions and mental health recovery movements -- Antisocial personality disorder, criminality, and substance use disorders -- Treating chemically dependent clients who have been exposed to trauma -- Blending addictions counseling with grief therapy -- Recovery management and the use of recovery coaches -- Motivational interviewing -- Using motivational incentives -- Engaging clients in cross-cultural counseling -- Reassessment of chronically relapsing clients.
Includes bibliographical references and index.
Keywords: Psychiatric social work; Evidence-based social work; Social case work; Addicts -- Counseling of; Mentally ill -- Counseling of; Counseling -- methods; Social Work, Psychiatric -- methods; Evidence-Based Practice; Substance-Related Disorders -- therapy; Addicts -- Counseling of; Evidence-based social work; Mentally ill -- Counseling of; Psychiatric social work; Social case work